1988
DOI: 10.1128/mcb.8.9.3761
|View full text |Cite
|
Sign up to set email alerts
|

Key features of heat shock regulatory elements.

Abstract: The promoters of heat shock protein genes are among the best-studied inducible eucaryotic promoters. Regions responsible for heat regulation have been identified previously by deletion experiments with several different heat shock genes. In this paper the critical importance of two novel features of heat shock regulatory elements was investigated. First, the elements were modular and, as a consequence, displayed a characteristic 5-nucleotide periodicity produced by multiple GAA blocks that were arranged in alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
287
0
5

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 545 publications
(299 citation statements)
references
References 51 publications
7
287
0
5
Order By: Relevance
“…Upstream of the MDJ7 open reading frame, at positions -28 and -88 with respect to the translational start codon, are two potential TATA boxes. Furthermore, the MDJ7 open reading frame is preceded by several weak matches to the heat shock element nGAAnnlXn (Amin et al, 1988;Young and Craig, 1993) and five copies of the CCCCT motif reported to be involved in heat shockfactor-independent gene induction (Kobayashi and McEntee, 1993) (Figure 1). The heat inducibility of MDJl was tested by Northern blot analysis, which revealed a 2-to 3-fold transient increase of transcript abundance upon shift of the cells from 24% to 37% (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Upstream of the MDJ7 open reading frame, at positions -28 and -88 with respect to the translational start codon, are two potential TATA boxes. Furthermore, the MDJ7 open reading frame is preceded by several weak matches to the heat shock element nGAAnnlXn (Amin et al, 1988;Young and Craig, 1993) and five copies of the CCCCT motif reported to be involved in heat shockfactor-independent gene induction (Kobayashi and McEntee, 1993) (Figure 1). The heat inducibility of MDJl was tested by Northern blot analysis, which revealed a 2-to 3-fold transient increase of transcript abundance upon shift of the cells from 24% to 37% (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Stressinduced activation of Hsf1 involves trimerization, acquisition of DNA-binding activity, and translocation to the nucleus (Baler et al 1993;Sarge et al 1993). In the nucleus, Hsf1 binds to heat shock element (HSE) sequences present in the promoter regions of Hsps (Amin et al 1988). In addition, regulation of Hsf1-mediated transcriptional activity is mediated by both constitutive and stress-inducible phosphorylation (Kline and Morimoto 1997;Holmberg et al 2001Holmberg et al , 2002Guettouche et al 2005).…”
Section: Figmentioning
confidence: 99%
“…The HSEs for heatresponsiveness are located in the 5 0 -flanking sequences of the HSP70 genes that contain triplet repeats of nGAAn, a nucleotide recognition motif/sequence (Pelham, 1982). A minimum of three 5-bp modules are required to form a functional HSE (Amin et al, 1988). The heat shock domain on the HSP70 promoter lies between À 107 and À 68, relative to the transcription initiation site, with the HSE centered at À 100.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%